Sensing uniaxial tensile damage in fiber-reinforced polymer composites using electrical resistance tomography. (19th July 2016) - Lestari, Wahyu; Pinto, Brian; La Saponara, Valeria; Yasui, Jennifer; Loh, Kenneth J
Abstract: This work describes the application of electrical resistance tomography (ERT) in sensing damage in fiber-reinforced polymer composites under uniaxial quasi-static tension. Damage is manifested as numerous matrix cracks which are distributed across the composite volume and which eventually coalesce into intralayer cracks. Hence, tensile damage is distributed throughout the volume, and could be more significant outside the sensor area. In this work, tensile damage of unidirectional glass fiber-reinforced polymer composites (GFRP) and plain weave carbon fiber-reinforced polymer composites (CFRP) is sensed by utilizing a spray-on nanocomposite sensor, which is then instrumented by boundary electrodes. The resistance change distribution within the sensor area is reconstructed from a series of boundary voltage measurements, and ERT is implemented using a maximum a posteriori approach and assumptions on the type of noise in the reconstruction. Results show that this technique has promise in tracking uniaxial damage in composites. The different fiber architectures (unidirectional GFRP, plain weave CFRP) give distinct features in the ERT, which are consistent with the physical behavior of the tested samples.